Construction and Characterization of a Vesicular Stomatitis Virus Chimera Expressing Schmallenberg Virus Glycoproteins - Huijuan Guo (Veterinary Sciences, 2025)
Schmallenberg virus (SBV) is a negative-sense RNA virus transmitted by insect vectors, causing arthrogryposis-hydranencephaly syndrome in newborn ruminants. Since its discovery in Germany and the Netherlands in 2011, SBV has rapidly spread across multiple European countries, resulting in significant economic losses in the livestock industry. With the increasing global animal trade and the expanded range of insect transmission, the risk of SBV introduction into non-endemic regions is also rising. As the gold standard for serological testing, the virus neutralization test (VNT) is crucial for tracking the spread of SBV and evaluating the efficacy of vaccines. However, in non-endemic regions, the lack of local viral strains and the biosafety risks associated with introducing foreign strains pose challenges to the implementation of VNT. In this study, we employed reverse genetics techniques using vesicular stomatitis virus (VSV) to substitute the VSV G protein with the envelope glycoproteins of SBV, thereby successfully generating and rescuing the recombinant virus rVSVΔG-eGFP-SBVGPC. The recombinant virus was then thoroughly characterized in terms of SBV Gc protein expression, viral morphology, and growth kinetics. Importantly, rVSVΔG-eGFP-SBVGPC exhibited SBV-specific cell tropism and was capable of reacting with SBV-positive serum, enabling the measurement of neutralizing antibody titers. The results suggest that this recombinant virus can serve as a feasible alternative for SBV neutralization tests, with promising potential for application in serological screening and vaccine evaluation.